THE EFFECT ORGANIZATIONAL INTEGRITY OF IN REDUCING SOME NEGATIVE BEHAVIORS IN THE WORKPLACE: A SURVEY OF A SAMPLE OF WORKERS AT THE DIWANIYAH BRANCH OF THE GENERAL AUTHORITY FOR TAXATION - Asmaa abdulwaheid malik alghnimi; Israa Qasim Yaseen; Alaa Qsim Yaseen (European Journal of Interdisciplinary Research and Development, 2024)
The current research aims to develop a set of proposed measures derived from the organizational integrity portal in order to reduce negative behaviors at work. organizations whose integrity is consistent with the goals are more successful and advanced because integrity reduces the chances of committing violations and reveals unethical behaviors in organizations and enables them to respond to negative behaviors at work resulting in several disadvantages, including leaving work, absence and late at work. in this context, those interested realized the strong link that connects organizational integrity aggressiveness. It should be noted that establishing a culture of organizational integrity in any organization includes a set of stages, including understanding the importance of organizational integrity, its necessity and benefits for the individual and the organization, clarifying the positives of its application and realizing the danger of the absence of organizational integrity from the organization. the study also recommended the need to apply honest practices within the organization.